2019
DOI: 10.3171/2019.9.focus19608
|View full text |Cite
|
Sign up to set email alerts
|

Primary pain generator identification by CT-SPECT in patients with degenerative spinal disease

Abstract: OBJECTIVEAxial spinal pain generators are difficult to identify using current diagnostic modalities. Merging CT with SPECT (CT-SPECT) scans allows for accurate identification of areas with increased osteoblastic activity, which may reflect pain generators. In this study, the authors aimed to evaluate the degree of pain improvement in patients who underwent surgery, addressing primary pain generators identified by CT-SPECT.METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Increasing evidence exists on the relationship between pain-causing DDD or facet arthropathy and SPECT positivity [ 6 , 24 ]. These findings have been recently confirmed by surgical studies [ 3 , 21 ]. However, the evidence for the effect of surgical treatment of SPECT-positive lumbar degeneration is not conclusive because of the small number of operated cases, combining different surgical techniques and single- and multi-level fusions in different areas of the spine [ 25 ].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Increasing evidence exists on the relationship between pain-causing DDD or facet arthropathy and SPECT positivity [ 6 , 24 ]. These findings have been recently confirmed by surgical studies [ 3 , 21 ]. However, the evidence for the effect of surgical treatment of SPECT-positive lumbar degeneration is not conclusive because of the small number of operated cases, combining different surgical techniques and single- and multi-level fusions in different areas of the spine [ 25 ].…”
Section: Introductionsupporting
confidence: 65%
“…Tender et al also found significant improvement in their 23 patients undergoing lumbar fusion (only 13 for single-level SPECT + DDD). The VAS score for axial pain decreased from 9.35 (± 0.7) preoperatively to 4.87 (± 2.3) 6 months postoperatively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A potential limitation arises from the fact that patient-reported neck pain before surgery was collected through phone calls. However, this is a commonly used method in observational studies on this topic [ 7 , 20 ]. To minimize potential information bias, professionals collecting patient-reported outcome data are trained to do so and are blinded to whether patients were submitted to an SPECT-CT before the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…22 A retrospective analysis of 48 patients, who underwent SPECT/CT to help identify the pain generator in neck and lower back pain and subsequently had cervical or lumbar fusion, noted a significant improvement in self-reported pain scores at 6 months postsurgery, suggesting that SPECT/CT may have some diagnostic advantages over current imaging modalities in correctly identifying pain generators in axial spine disease. 23 A smaller prospective study of back pain in older adult patients ( n = 5) demonstrated the usefulness of SPECT/CT in correctly identifying the specific cause of pain in patients with lumbar degenerative disease. 24…”
Section: Reviewmentioning
confidence: 99%